International financial reporting standards : a practical guide - Greuning, Hennie van.; Greuning, Hennie van.; World Bank. (Washington, D.C. : World Bank, 2005)
Giving readers a broad and basic understanding of the key issues for each International Financial Reporting Standard, this book provides a quick reference for managers and executives in the private and public sectors who may not have a strong background in accounting.
Rev. ed. of: International accounting standards. 2001.
oif 13/03/15
Loan
Keywords: Accounting; Financial statements